Reviewing the literature on the tripartite cycle containing digital building permit, 3D city modeling, and 3D property ownership. (October 2022) - Guler, Dogus; Yomralioglu, Tahsin
Abstract: There is an increasing trend for digitalization because of the developments in Information and Communications Technologies (ICTs). One of the topics that digitalization might be helpful is the building permit issuing that has some drawbacks in terms of the duration of finalization, a large number of documents, and the transparency of processes. Another topic is the need for updating three-dimensional (3D) city models that are beneficial for the effective management of urban areas in the sense of a wide range of subjects such as land-use planning, disaster response, and underground infrastructure monitoring. Apart from these topics, 3D land administration that copes with the ownership problems due to the ever-increasing existence of multilayered buildings in the built environment is gaining importance. Many studies mention that the interrelation among these topics can be advantageous because of exploiting the common digital building models namely Building Information Models (BIMs). It is therefore focused on a research question as follows: Is there a potential for integrating the digital building permit procedures, 3D city model updating, and 3D registration of property ownership as a tripartite cycle? This paper accordingly aims to review the scientific literature on the vision of the tripartite cycle to provide an insight into possible integration among its parts. The methodology contains an elaborate examination of the previous research that is collected from scientific databases and is categorized based on aspects of the tripartite cycle. Following the discussion of the literature, the recommendations are provided in the sense of the vision of the tripartite cycle. Highlights: Digital building permitting, 3D city model updating, and 3D cadastre can be considered as interrelated. Digitalization is evident in a wide range of sectors and industries, for example, land administration. As-built BIMs are significant because of providing digital information flow regarding buildings. The harmonized international standards can improve processes pertaining to the built environment.